The Victorian Women on Farms Gatherings: A Case Study of the Australian "Women in Agriculture" Movement - Pini, Barbara; Panelli, R.; Dale-Hallet, L. (Blackwell Publishing Asia, 2007)
This article provides a case study of the Victorian Women on Farms Gatherings (WOFG) to redress the lack of attention political historians have paid to farm women. Using materials collected by Museum Victoria, we trace the reasons for farm women's activism during the latter part of the twentieth century, and document the activities and outcomes of the Gatherings held annually since 1990. Our study demonstrates that farm women see politics as multi-faceted and heterogeneous. In short, there are no clear binaries between the political and non-political. This demonstrates the need to avoid masculinist and conventional definitions of politics, which obscure the political activities of women. Politics should not be conceptualised in a manner which associates women as a group with informal and non-traditional political activity. This simply reinscribes the types of binaries that have encouraged the omission of women from political history.